Examining Internal and External Drivers of Profitability in Indonesian Rural Banks: Evidence from Panel Data Analysis - Tampubolon, Gordon Pardamean; Lutfi, Lutfi (Jurnal Samudra Ekonomi dan Bisnis, 2026)
This study investigates the internal and external determinants of profitability in Indonesian Rural Banks (BPR), with credit risk acting as a mediating variable. Internal factors include capital adequacy, bank size, operational efficiency, and credit distribution, while external factors comprise inflation and interest rates. The study utilizes a panel data regression method, covering 23 conventional BPRs operating in West and Central Kalimantan from 2019 to 2023. The findings reveal that capital adequacy negatively affects profitability, whereas operational efficiency and credit distribution exert positive influences. However, excessive credit expansion leads to rising non-performing loans (NPL), which subsequently diminish profitability. Interest rates and inflation have no significant impact. This research contributes to the literature by empirically confirming the mediating role of credit risk in rural bank performance and offers strategic insights for policymakers and rural bank managers to strengthen financial sustainability.